Valued Objects Dynamics and Adaptability of Domestic Workspaces - Elmira Zanjabila; Kristanti Dewi Paramita (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2023)
This paper discusses the dynamic value of objects that influence the spatial organization of a home-based workspaces. Spatial organization of workspace at home becomes significant with the emerging work-from-home arrangement during and post COVID-19 pandemic. The physical and psychological needs of working from home require adaptations on the domestic setting through the use and placement of objects in relation to how humans produce and experience space. This paper examines the value mechanism of remote workers with regards to their everyday objects and how such mechanism affects the overall workspace organization them. The study explores the workspace of 3 remote workers with different activities and preferences. The study shows that the dynamic value of objects shapes the workplace arrangements, enabling better accessibility, supporting the need for comfortable and pleasant qualities of space, as well as demonstrating self-identity. The study expands discussions on the spatial adaptation driven by dynamic system of objects.